Pengaruh Pengalaman Kerja, Independensi Dan Kompetensi Terhadap Kualitas Audit (Studi Kasus Pada Kantor Akuntan Publik di Wilayah Jakarta Timur dan Bekasi) - Alvin, Arya Alam; Karsam, Karsam; Syafrudin, Syafrudin; Gantino, Rilla (Asosiasi Dosen Akuntansi Indonesia, 2023)
The purpose of this study was to determine the effect of work experience, independence, and competence on audit quality at Public Accounting Firms in East Jakarta and Bekasi. The population in this study were auditors, including partners in the KAP in East Jakarta and Bekasi, with a sample of 100 respondents. Data Collections using the questionnaire method, the data analysis method using multiple linear regression and using the SPSS computer system version 25, which concludes that each variable of Work Experience, Independence, and Competence affects audit quality. Simultaneously, work experience, independence, and competence affect audit quality